Correction: Immich et al. Evaluation of Antimicrobial Properties, Cell Viability, and Metalloproteinase Activity of Bioceramic Endodontic Materials Used in Vital Pulp Therapy. J. Funct. Biomater. 2024, 15, 70 - Felipe Immich; Durvalino de Oliveira; Juliana Silva Ribeiro de Andrade; Andressa da Silva Barboza; Carlos Enrique Cuevas-Suárez; Adriana Fernandes da Silva; Wellington Luiz de Oliveira da Rosa; Álvaro Henrique Borges; Neftali Lenin Villarreal Carreno; Evandro Piva; Rafael Guerra Lund (Journal of Functional Biomaterials)
Error in Figure 3 [...]